Anatomi Kayu Palele (Castanopsis javanica) Wood Anatomy of Palele (Castanopsis javanica) - Nani Husein (Masyarakat Peneliti Kayu Indonesia, 2004)
As an effort to overcome scarcity of raw material for wood processing industries, utilization of wood from various lesser known species should be conducted. Wide prospects of utilization will be opened when complete data of species and their properties are available.The aims of this research is to get microscopic features concerning to the wood anatomical structure of Palele (Castanopsis javanica) at the vertical and radial directions. Observation of wood anatomical structures in accordance to International Association of Wood Anatomist standard; includes diameter, height and amount of vessel; also height, width and amount of wood rays; percentage of vessels, percentage of rays, axial parenchyma and percentage of fiber, fiber diameter, fiber lumina, and fiber wall thickness.In this research it is found that wood vessels are oval to round, solitary vessels in radial arrangement, vessels consist of rare tylosis, wood diffuse porous, alternate pits with simple plate perforation. Wood rays is uniseriate heterogeneous, two types of axial parenchyma, i.e. : apotracheal scalariform and paratracheal with narrow short bands and wavy. Fiber quality includes in category class II. This wood has medium to long size fiber with thin walled and wide of lumina. It is predicted that wood fiber of Palele can be used as raw material for paper with smooth surface and medium strength.